Neofrancoism and the Problem of Territorial Integrity of Modern Spain - A. V. Dementiev (MGIMO University Press, 2019)
The article is devoted to the strengthening of right-wing and populist sentiments observed in Spanish society in recent years, which is largely a consequence of both ethno-national conflicts, primarily in Catalonia, and of social and ideological confrontations that have become aggravated in the country. There is an increase in the influence of neo-traditionalists and neo-conservatives, whose calls to protect the territorial integrity of the country, the Christian values and historical traditions of the Spanish nation are heard louder, echoing Franco's ideological and political heritage. Neo-francoists, neo-phalangists, monarchists, carlists, and some military circles in Spain praising now the contribution of the dictatorial regime to the historical and socio-economic development of the country in the 20th century. The article cites facts proving that the basic tenets of Francoism, associated primarily with the preservation of the territorial integrity of the country and the unity of the Spanish nation, are finding welcome response in modern Spain. With the growth of separatist aspirations in the regions the nationalism in the form of neo-Francoism, has recently acquired more and more real political power. The conclusion is proved by the success of the right-wing Vox party in the elections to the regional parliament of Andalusia in December 2018. If the current trends continue, Spanish ultranationalists and neo-francoists will be represented not only in regional parliaments, but will also receive mandates in the General Cortes and the European Parliament.